The academic anxiety of students in pandemic era - Ulin Nihayah; Ahmad Shofwan Ats-Tsauri Sadnawi; Nuha Naillaturrafidah (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2021)
Purpose - The purpose of this study was to describe the problems of academic anxiety that occur in college students as a result of the COVID pandemic that occurs and alternative solutions to overcome them in the perspective of counseling guidance.Method - The research method used was descriptive quantitative, where the author conducts a survey to students who experience academic anxiety during the pandemic. The sample of the study consisted of 28 students from 9 universitiesResult - The results of the research conducted are that the psychological anxiety disorders due to online lectures related to the influence of online lectures on student sleep patterns as much as 32.1%, 17.9% have difficulty sleeping, and 11.1% wake up sluggish. In addition, there are anxiety disorders due to online lectures that have a physical impact on the condition marked by 42.9% feeling lethargic and unmotivated, 14.3% achy, 28.6% eye strain, 14.8%, so it has an impact on mastery of the material with the result that 82.1% can absurb master the material, and the rest did not master the material.Implications – This study can be used to improve the problems of academic anxiety that occur in college students as a result of the COVID pandemic.Originality - This research is the study analysis student academic-anxiety in dealing with online lectures by using the analysis of counseling guidance.***Tujuan - Tujuan penelitian ini untuk mendeskripsikan permasalahan academic anxiety yang terjadi pada mahasiswa akibat pandemi COVID yang terjadi dan alternatif solusi untuk mengatasinya dalam perspektif bimbingan konseling.Metode - Metode penelitian yang digunakan adalah deskriptif kuantitatif, dimana penulis melakukan survey kepada mahasiswa yang mengalami academic anxiety selama masa pandemi. Sampel penelitian terdiri dari 28 mahasiswa dari 9 universitas.Hasil - Hasil penelitian menunjukkan bahwa gangguan kecemasan psikologis akibat kuliah online terkait pengaruh kuliah online terhadap pola tidur mahasiswa sebanyak 32,1%, sulit tidur 17,9%, dan bangun lamban 11,1%. Selain itu terdapat gangguan kecemasan akibat kuliah online yang berdampak pada kondisi fisik yang ditandai dengan 42,9% merasa lesu dan tidak bersemangat, 14,3% pegal, 28,6% mata tegang, 14,8% sehingga berdampak pada penguasaan materi. dengan hasil 82,1% dapat menguasai materi, dan sisanya tidak menguasai materi.Implikasi - Penelitian ini dapat digunakan untuk memperbaiki masalah kecemasan akademik yang terjadi pada mahasiswa akibat pandemi COVID.Originalitas - Penelitian ini merupakan penelitian analisis kecemasan akademik mahasiswa dalam menghadapi perkuliahan online dengan menggunakan analisis bimbingan konseling.